Localization of dendritic cells and T cells within the tumor microenvironment in different types of skin cancer - Marina Wanner; Anna Brunner; Daniela Ortner; Christoph H. Tripp; Martin Hermann; Selina Neurauter; Barbara Del-Frari; Van Anh Nguyen; Patrizia Stoitzner (Histochemistry and Cell Biology, 2026)
Immunophenotyping of tumor-infiltrating immune cells is increasingly important for understanding the tumor microenvironment (TME), particularly in the diagnosis and treatment of skin cancer. CD1a + dendritic cells (DC) initiate T cell activation by presenting tumor antigens, while T cells directly target tumor cells. Analyzing their spatial distribution in different types of skin cancer can provide insights into immune response patterns. To characterize the immune cell composition within the TME, we performed immunofluorescence staining for CD1a and CD3 on formalin-fixed, paraffin-embedded (FFPE) samples from actinic keratoses ( n = 18), squamous cell carcinoma ( n = 23), basal cell carcinoma ( n = 19), and melanoma ( n = 22), with nevi ( n = 16) and healthy skin ( n = 9) as controls. Immune cells were quantified across four tumor compartments: intratumoral, tumor margin, intraepidermal, and intradermal. Both CD1a + DC and CD3 + T cells were detected across all tumor entities, displaying distinct spatial distribution patterns. DC were enriched intratumorally and within the epidermis, whereas T cells predominantly accumulated at the tumor margin (main effect of region, p < 0.001). Melanoma exhibited significantly fewer DC at the tumor margin while maintaining strong T cell infiltration. Overall, the immune architecture of skin tumors is highly compartmentalized, characterized by region-specific DC and T cell distributions. These findings underscore the relevance of spatial immune profiling for understanding immune escape mechanisms and informing immunotherapeutic strategies.

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Intraguild predation in pioneer predator communities of alpine glacier forelands - Lorna Raso; Daniela Sint; Rebecca Mayer; Simon Plangg; Thomas Recheis; Silvia Brunner; Rüdiger Kaufmann; Michael Traugott (Molecular Ecology, 2014)
Pioneer communities establishing themselves in the barren terrain in front of glacier forelands consist principally of predator species such as carabid beetles and lycosid spiders. The fact that so many different predators can co‐inhabit an area with no apparent primary production was initially explained by allochthonous material deposited in these forelands. However, whether these populations can be sustained on allochthonous material alone is questionable and recent studies point towards this assumption to be flawed. Intraguild predation ( IGP ) might play an important role in these pioneer predator assemblages, especially in the very early successional stages where other prey is scarce. Here, we investigated IGP between the main predator species and their consumption of C ollembola, an important autochthonous alternative prey, within a glacier foreland in the Ö tztal ( A ustrian A lps). Multiplex PCR and stable isotope analysis were used to characterize the trophic niches in an early and late pioneer stage over 2 years. Results showed that intraguild prey was consumed by all invertebrate predators, particularly the larger carabid species. Contrary to our initial hypothesis, the DNA detection frequency of IGP prey was not significantly higher in early than in late pioneer stage, which was corroborated by the stable isotope analysis. Collembola were the most frequently detected prey in all of the predators, and the overall prey DNA detection patterns were consistent between years. Our findings show that IGP appears as a constant in these pioneer predator communities and that it remains unaffected by successional changes.

Pharmacological manipulations of interval timing using the peak procedure in male C3H mice - Fuat Balci; Elliot A. Ludvig; Jacqueline M. Gibson; Brian D. Allen; Krystal M. Frank; Bryan J. Kapustinski; Thomas E. Fedolak; Daniela Brunner (Psychopharmacology, 2008)

Astrocytes protect the CNS: antigen-specific T helper cell responses are inhibited by astrocyte-induced upregulation of CTLA-4 (CD152) - Ulrike Gimsa; Anita ren; Pushpa Pandiyan; Daniela Teichmann; Ingo Bechmann; Robert Nitsch; Monika C. Brunner-Weinzierl (Journal of Molecular Medicine, 2004)

Blood sampling methodology is crucial for precise measurement of plasma catecholamines concentrations in mice - Eric Grouzmann; Claudia Cavadas; Daniela Grand; Martine Moratel; Jean-Franois Aubert; Hans R. Brunner; Lucia Mazzolai (Pflügers Archiv - European Journal of Physiology, 2003)

The DBA/2J strain and prepulse inhibition of startle: a model system to test antipsychotics? - Berend Olivier; Christina Leahy; Tanner Mullen; Richard Paylor; Vincent E. Groppi; Zoltan Sarnyai; Daniela Brunner (Psychopharmacology, 2001)

Use of a photoactivable GM1 ganglioside analogue to assess lipid distribution in caveolae bilayer - Marina Pitto; Joseph Brunner; Anita Ferraretto; Daniela Ravasi; Paola Palestini; Massimo Masserini (Glycoconjugate Journal, 2000)

Normal Ascorbic Acid in Cerebrospinal Fluid of Patients with Infantile Neuronal Ceroid-Lipofuscinosis - Jörn Oliver Sass; Daniela Skladal; Michaela Brunner-Krainz (Metabolic Brain Disease, 1999)